Analisis Lama Waktu Penyediaan Berkas Rekam Medis Rawat Jalan untuk Pasien Lama Poli Bedah Onkologi di RSAL dr. Ramelan Surabaya Tahun 2020 - Bastin Nur Aliefia; Gamasiano Alfiansyah; Indah Muflihatin (Politeknik Negeri Jember, 2020)
Polyclinic at RSAL dr. Ramelan Surabaya which has the most number of patient visits every day is poly surgical oncology than other poly surgery which is ± 55 - 60 patients, here researchers see that with the many requests for medical record files, the supply of medical record files must be as fast as possible and must still meet existing standards. But in reality the supply of medical record files still exceeds the standard. The results of the observations I made to search for 1 file took 5 minutes until the file was recorded in the register of each poly, aiming that the file with no. The RM has been sent and then barcoded or sent via SIMRS, it should be marked that the medical record file must already be in the clinic but here the file is still placed on the table very long which is about 15 minutes and can also be more than it should be sent to the polyclinic. That way the file does not get to the clinic according to the Hospital Minimum Service Standards (SPM). The aim is to find out how long it takes to provide medical records in outpatients for poly surgical oncology patients at RUMKITAL Dr. Ramelan Surabaya. This type of research is qualitative. Data collection techniques in the form of interviews and observations. The population in this study were all outpatient medical record files for oncology surgery patients in March 2020. The results obtained from the study were the length of time the provision of outpatient medical record files for old poly surgical oncology patients exceeded the established standard that required an average time 11 minutes for each file arrived at the polyclinic.